Third Eye Café: Sustaining Mainstream Transgender Employment. Issue 1 (March 2022) - Mehta, Nikhil Kewal Krishna
Working with transgender people or knowing about them is an intriguing subject for many (Revathi, 2010, The Truth About Me: A Hijra Life Story, New Delhi: Penguin Books). This case offers readers an opportunity to quench their curiosity and have a reasonable understanding of transgender people and their employment. The case weaves an entrepreneurial conflict of interest with the threads of entrepreneurial challenges and transgender employees. While it offers a path-breaking opportunity to understand marginalized transgender people, it ensures that learners understand and develop sensitivity to deal with issues of the mainstream employment of transgender people. The given case paves the way for the participants to think about ways of transgender inclusion and acclimatization in mainstream jobs. In the process of paving these ends (or beginnings), participants acknowledge their understanding of issues such as integrated business models, enlightened stakeholder theory, and Bourdieu theory of practice.